Properties of the language in the development of culture - Sharipova Feruza Negmatulloevna; Saidova Parvina (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article under discussion reveals the specific features of the language in the development of culture. The author of the article believes that for many centuries now, the problem of the relationship between language and culture has been in the minds of many famous scholars, but to this day the issue remains debatable: some believe that language refers to culture as part of the whole; others believe that language is only a form of cultural expression.